Implications and Legal Aspects of Online Gambling According to Law No. 11 of 2008 concerning Electronic Information and Transactions - Batua Hamonangan; T. Riza Zarzani; Sumarno (International Journal of Society and Law, 2024)
Online gambling has become a significant phenomenon in the current digital era, giving rise to various implications and legal aspects that need to be considered. Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE) is one of the relevant legal foundations in regulating online gambling activities. The legal implications of online gambling according to the ITE Law include recognition of electronic evidence, law enforcement against violations that occur online, and protection of consumers involved in online gambling transactions. Legal aspects that need to be considered include determining legal sanctions for online gambling players, the obligation of organizers to comply with the provisions of the ITE Law, and efforts to prevent and overcome harmful online gambling practices. By understanding the implications and aspects of this law, it is hoped that a safer and more orderly digital environment can be created for people in their online activities.